Implications Of The Legal Form Of Roe For Company Management - Suparman, Yusup; Mbunai, La Ode (CV Putra Publisher, 2026)
This study discusses the relationship between corporate legal form and the application of Return on Equity (ROE) as a financial performance indicator in corporate management. Using a normative legal approach, this study shows that the legal form of a company greatly influences the use of ROE in managerial practices and sustainable corporate governance. ROE is used to measure the effectiveness of equity capital in generating profits, which forms the basis for evaluating profitability and managerial efficiency. In the Indonesian legal context, although ROE is not explicitly regulated in legislation, its application is supported by various regulations that emphasise transparency, accountability, and integrity in financial reporting. This study also highlights the role of ROE in strategic decision-making such as investment, dividend distribution, and business expansion, as well as the legal risks arising from ROE manipulation.